Experimental investigation of the effect of simultaneous nitrogen, hydrogen and EGR addition in a biodiesel operated CI engine. Issue 6 (2nd November 2017) - Kumar, R. Senthil; Loganathan, M.; Gunasekaran, E. James
ABSTRACT: Internal combustion engines continue to dominate in many fields like transportation, agriculture and power generation. Among the various alternative fuels, hydrogen is a long term renewable and less polluting fuel. Overcoming diesel engine emissions, especially NOx, requires investigation of new systems which can potentially steer the automobile industry towards further emissions reduction. Addition of hydrogen (H2 ) and nitrogen (N2 ) with exhaust gas recirculation (EGR) can lead to a new generation of low polluting compression ignition (CI) engines. In this experiment the H2, N2 and exhaust gas were inducted into the inlet manifold with inlet air. The experiments were conducted on a four-stroke, single-cylinder, water-cooled, direct injection (DI) diesel engine at a speed of 1500 rpm. The H2 and N2 were stored in a high pressure cylinder and supplied to the inlet manifold through water and air based flame arrestor at 2 bar pressure. The EGR valve is used to control the EGR to the inlet of the engine. Initially the engine was run for different H2 flow rate and optimized for maximum BTE. Then this (maximum BTE) flow rate of H2 was taken to optimize the EGR rate for 5%, 10% and 20%. The engine was run by different flow rates of N2 namely 2%, 3% and 4% with optimized EGR and H2 flow rate. The engine performance, emission and combustion parameters were analyzed at this condition which gives low NOx emission. The fuel used was a blend of 20% biodiesel and 80% diesel called B20. The experimental results show that the brake thermal efficiency (BTE) increased due hydrogen addition but the addition of EGR and N2 decreased the BTE. NOx emission decreased due to addition of EGR and N2 . While the induction of H2 tended to decrease the emission of HC and CO, the addition of N2 and EGR with H2 tended to increase the above emissions. The heat release rate and cylinder pressure slightly decreased due to addition of N2 with H2 and EGR.